Eu quero, eu posso, mas será que eu consigo? Fenômeno Impostor em pós-graduandos stricto sensu da área de negócios - Meurer, Alison Martins (2021)
Objective: to identify the factors that characterize the Phenomenon Phenomenon of stricto sensu graduate students from the business area based on the Clance Impostor Phenomenon Score (CIPS) validation. Method: the research counted with the valid participation of 613 students in the pre-test phases and 1,816 students in the final collection. The data were analyzed using descriptive statistics, confirmatory factor analysis and exploratory factor analysis. Results: CIPS indicators pointed to a two-dimensionality, with one of the factors characterizing feelings of falsehood and underestimation and the other related to luck or chance. The results also point out that the imposing feelings in the business area are more focused on the perception of falsehood or underestimation, than on the attribution of success to luck or chance. Contributions: the identification of the Impostor Phenomenon is important so that these feelings can be shaped in order not to limit and hinder the academic development and professional career of the students.